The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1067/mva.2002.126087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraluminal thrombus on wall stress in patient-specific models of abdominal aortic aneurysm

Abstract: The presence of ILT alters the wall stress distribution and reduces the peak wall stress in AAA. For this reason, ILT should be included in all patient-specific models of AAA for evaluation of AAA wall stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
324
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(358 citation statements)
references
References 0 publications
10
324
0
11
Order By: Relevance
“…14 Other authors suggest the mural thrombus could be a protecting factor, reducing the hemodynamic stress on the AAA wall, such reduction being more marked in large and well organized thrombi, whereas it could also be found in small ones. 10 A study of 78 autopsies reported that 62% (49) of the aneurisms suffered rupture on the posterior wall. However, these authors did not associate a role of protection to the thrombus, since it was present in 80% (62) of the cases, at the site of rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Other authors suggest the mural thrombus could be a protecting factor, reducing the hemodynamic stress on the AAA wall, such reduction being more marked in large and well organized thrombi, whereas it could also be found in small ones. 10 A study of 78 autopsies reported that 62% (49) of the aneurisms suffered rupture on the posterior wall. However, these authors did not associate a role of protection to the thrombus, since it was present in 80% (62) of the cases, at the site of rupture.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] An intraluminal thrombus (ILT) is present in approximately 75% of all cases of AAA. 10 Recent studies suggest that the ILT is an active pathogenic factor for AAA. [11][12] Adolph et al, 11 have demonstrated the biological activity of the thrombus by the presence of activated cells and by the relative permeability of the aneurismatic wall to formed elements of the blood.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the vessel stress to vessel strength is regarded as an alternative tool to conventional diameter criteria, which may be insufficient in small aneurysms. In computational simulations, vessel stress is calculated as a function of the vessel diameter [7,34], wall thickness [36,37], asymmetry [14,18,34,36], tortuosity [21], material property [17,24,29,38], calcification [15,22], intraluminal thrombus (ILT) [5,15,16,33], and blood flow [4, 9, 13, 14, 17, 20, 25, 26, 28-30, 32, 35-41]. Blood vessel strength is measured by ex vivo studies [11,12,23,31,44] or estimated by effective features such as ILT existence, sex, and genetic vulnerability [10].…”
mentioning
confidence: 99%
“…However, very recently [7] and [3] reported extensive studies on the material properties of thrombus. The mean thrombus shear modulus that they found (1.7 ± 1.3 kPa) is much lower than the values assumed in [9,48], the role of thrombus in wall-stress analysis may therefore be overestimated. The elasticity of thrombus is several orders higher than that of the vessel wall [6], which may mean that thrombus could be neglected during the wall-stress simulations.…”
Section: Wall-stress Modelingmentioning
confidence: 56%
“…Intraluminal thrombus has been incorporated in the finite-element models in several other studies [9,21,48]. In [48] and [9] a significant influence was reported of thrombus on the outcome of the stress calculations. However, very recently [7] and [3] reported extensive studies on the material properties of thrombus.…”
Section: Wall-stress Modelingmentioning
confidence: 99%